Terapi Nebulizer Dengan Active Cycle Breathing Technique Pada Pasien Asma Bronkial - Wijaya, Sapondra; Muliyadi, Muliyadi; Susmini, Susmini; Trisnawati, Vivi (Jurusan Keperawatan, Poltekkes Kemenkes Palembang, 2024)
Background: Asthma attacks can cause blood oxygen levels to become very low, resulting in hypoxemia. This condition can cause confusion, lethargy, and even loss of consciousness and death. Immediate action is needed to overcome this condition, one of which is nebulizer therapy with Active Cycle of Breathing Techniques. This study aims to describe the implementation of nebulizer therapy with Active Cycle of Breathing Techniques. Methods: Descriptive research with a case study approach. Application of nebulizer therapy and active cycle breathing technique in bronchial asthma patients in the Emergency Room of Siti Aisyah Hospital, Lubuklinggau City. There were 4 asthma patients who came to the Emergency Room given a combination of nebulizer therapy with Active Cycle of Breathing Techniques for about 20 minutes. Results: The breathing pattern of 4 subjects decreased by an average of 5 breaths, in Subject I from 30 x/minute to 23 x/minute. Subject II, from 26 x/minute to 22 x/minute, Subject III from 27x/minute to 22x/minute and in Subject IV from 24x/minute to 20x/minute. Wheezing sound before intervention, disappeared after intervention. Conclusion: The combination of pharmacological and non-pharmacological nebulizer therapy with salbutamol and Active Cycle Breathing Technique is effective for asthma patients in the ER.